Pengaruh Keunggulan Bersaing Terhadap Loyalitas Pelanggan - Bendyi Afrianto; Ahmad Kamaludin (Journal of Innovation in Management, Accounting and Business, 2023)
This study aims to determine the effect of competitive advantage on consumer loyalty. The research method used is descriptive and verification methods. The sample in this study were customers of Liang Julang "Raja Enak" Crackers, Kadipaten District, Majalengka Regency, with as many as 96 respondents. Data was collected using a questionnaire distributed to respondents. Based on research data, shows that competitive advantage has a significant effect on customer loyalty. The calculation of the regression obtained a constant value of 4.06 and a regression coefficient of 0.38. The constant value of 4.06 indicates that if there is no increase in the value of the competitive advantage variable, the price for customer loyalty is 4.06. The regression coefficient is 0.38 which shows that for each addition of one score, the value of competitive advantage will increase the score by 0.38 times. The calculation of the coefficient of determination also shows the contribution of competitive advantage to the ups and downs of customer loyalty by 59.96%. The conclusion of this study is that competitive advantage has an effect on customer loyalty in Liang Julang's " Raja Enak" crackers, Kadipaten District, Majalengka Regency.